FRI0023 Five-year progression of rheumatoid arthritis disease activity and quality of life in 2002 and 2011. have reductions in disease activity in recent years resulted in improvements in quality of life?. (12th June 2018) - Carpenter, L.; Norton, S.; Nikiphorou, E.; Kiely, P.; Dixey, J.; Creamer, P.; Walsh, D.; Young, A.; ,
Abstract : Background: The treat-to-target (T2T) approach, with earlier, aggressive treatment has resulted in improvements in rheumatoid arthritis (RA) outcomes 1, 2 . Whether these improvements have translated into improvements in patient reported outcomes is less clear. Studies have indicated declines in pain and function as well as depression and anxiety. However, these studies are limited to short follow-up periods or were restricted to cross-sectional, rather than longitudinal analyses. Objectives: To assess changes in 5 year progression rates for disease activity and patient reported outcomes in a prospective cohort of early RA patients between 2002 and 2011. Methods: The Early RA Network (ERAN) is a longitudinal prospective cohort study that recruited 1236 early RA patients from 2002 to 2011. DAS-28 and SF-36 were measured at baseline, 6 months, 12 months and then yearly. Multi-level linear regression were used to model 5 year progression rates of both DAS-28 and SF-36 in patients recruited between 2002–2011. Models controlled for sex and age and seropostivity at baseline. DMARD use at baseline was controlled for using propensity score weighting. Year of diagnosis was entered as a continuous variable, allowing for the mean of the outcome variables to be estimated for 2002 and 2011. Restricted cubic splines were used to account for non-linear progression over time. Results: Disease activity for patients diagnosed in 2011 demonstrated a statistically significant decrease at year 5 compared to patients diagnosed in 2002 (5 year estimated mean difference −0.35; 95% CI 0.22–0.49, p<0.001). Using the SF-36 measure, Physical Function, Bodily Pain, Vitality (indicating fatigue) and Mental Health indicated similar levels at year-5 between those patients diagnosed in 2011 to those diagnosed in 2002 (p>0.05). Mental health was similar to the normalised population mean of 50, irrespective of year diagnosed. However, levels of vitality/fatigue, function and pain remain less favourable for all early RA patients over the first 5 years. Conclusions: Although disease activity has shown a marked decline at 5 years between 2002 and 2011, there is little evidence that this has led to improvements of an equivalent magnitude in function, pain, fatigue and mental health. Treatment should also focus on improved function, pain management, fatigue and mental health as part of the T2T protocol. References: [1] Twigg S, et al. Fatigue, older age, higher body mass index and female gender predict worse disability in early rheumatoid arthritis despite treatment to target: A comparison of two observational cohort studies from the United Kingdom. Arthritis Care Res. (Hoboken). 2017. doi:10.1002/acr.23281 [2] Carpenter L, et al. Reductions in Radiographic Progression in Early Rheumatoid Arthritis Over Twenty-Five Years: Changing Contribution from Rheumatoid Factor in Two Multicenter UK Inception Cohorts. Arthritis Care Res. 2017;69. Disclosure of Interest: None declared